*The significance of p-ANCA in differing chronic amebic colitis from ulcerative colitis complicated with amebic colitis - Serap ARSLAN,; Yusuf AKCAN,; Ayşin BAKKALOĞLU,; Serdar TUNCER,; Emin KANSU,; Serhat ÜNAL,; Sibel ERGÜVEN,; Fikri CANORUÇ,; Bedri UZUNALİMOĞLU,; Burhan KAYHAN 0, (Turkish Journal of Gastroenterology, 2019)
-